Assessing the Effects of Shared Family Mealtimes on Family Functioning and Socialization among Students of the University of Cyberjaya during Movement Control Order (MCO) - Ahmad Neyaz Ansari; Pavithranair Murali; Qistina Irdina Kamarul Ariffin; Maria Zalina Abdul Rahim (Asian Journal of Medicine & Health Sciences, 2023)
Background: The Movement Control Order (MCO) had been imposed from 18th March 2020 due to the presence of a new strain of corona virus (COVID-19). The commencement of MCO included restriction of all face-to-face academic activities in all sectors of education in Malaysia which has forced university students to undergo online learning at their respective homes. This study aims to determine the effects of family functioning and well-being among university students in relation to the frequency of shared family meals throughout the commencement of MCO. Methods: A cross-sectional study was conducted among students of University of Cyberjaya of 18 years old and above. Respondents were chosen through stratified random sampling by categorising the students into different faculties and each student was chosen through random sampling. Data was collected online through a google form link and analysed using JASP. Results: A total of 137 respondents participated in this research. The frequency of shared family mealtime per week was not associated with depression, anxiety and stress as the p- value is more than 0.05 but a better level of family functioning was associated with decreased incidence of depression and anxiety. Conclusion: The shared family mealtimes among undergraduate University of Cyberjaya students has no significant correlation between depression, anxiety and stress. However, our study has proven that regular shared family mealtimes is associated with improved family functioning and socialisation which in return decreases the incidence of depression and anxiety.